Reasoning Adaptive Ability in Solving Questions Mathematics Logic Based on Learning Creativity - Annis Sholiha Suhanda; Triana Citra Lestari; Abdul Rozak (Etunas, 2023)
The purpose of this study was to analyze the adaptive reasoning skills by students' creativity in solving mathematical logic. This study uses a qualitative descriptive research method. The subject of the research was a 3rd grade student of IAIN Syekh Nurjati who was chosen by one of the students with high learning creativity, medium learning creativity, and low learning creativity. Use sampling techniques aimed at selecting subjects. The data collection techniques used were written tests, indirect communication techniques and interviews, while the tools in this study were adaptive reasoning tests, learning creativity questionnaires and interview guidelines. Use triangulation techniques to test the validity of the data. Data analysis was carried out through data simplification, data presentation and conclusion drawing. The results showed that students with high learning creativity met four indicators, namely, guessing, giving reasons for the truth of the statement, drawing conclusions from the statement, and testing the validity of the argument but did not meet the indicators of getting a model from mathematical symptoms, students with moderate learning creativity only met two indicators, namely submitting allegations and verifying the validity of arguments; students with low learning creativity only meet one indicator, namely providing reasons or evidence for statements.